PERANCANGAN MEDIA PEMBELAJARAN ORGAN PENCERNAAN BERBASIS GAME ROLE PLAYING UNTUK KELAS V SD - Novi Hartanto; Fitro Nur Hakim (STEKOM PRESS, 2020)
The low standard of values ​​for natural science shows that Indonesia is still lagging behind other countries. This can be seen from the data from the results of the PISA survey conducted by the OECD in 2003 which states that the standard for Natural Sciences in Indonesia is 360.16, while the standard for Natural Sciences (IPA) in the world is 484.84. This data shows that the average score of Natural Sciences subjects is still very low. There are many factors that underlie the low value of IPA in Indonesia. one of them is the assumption that this subject is difficult. In addition, students also find this subject boring and uninteresting. Therefore, this study intends to develop alternative media for fifth grade students to help them learn science, namely in the form of an RPG game that can be played via a computer.